2015
DOI: 10.1177/1359105315573432
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional eating behaviour, psychological well-being and adaptation to pregnancy: A study with women in the third trimester of pregnancy

Abstract: This study evaluated the prevalence and predictors of dysfunctional eating. Women in the third trimester of pregnancy participated in this study (N = 105). Dysfunctional eating was associated with a higher body mass index, enhanced negative body image, more somatic symptoms, poorer marital relationships, more negative attitudes regarding pregnancy and the baby and more emotional problems. A higher body mass index prior to the pregnancy, higher weight gain during pregnancy and a more negative perception of body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…One fair‐quality cross sectional study found that obsessive‐compulsive symptoms was positively associated with disordered eating during pregnancy above 28 weeks gestation (Mohamadirizi et al, ). Similarly, Goncalves et al () identified that increased obsessive‐compulsive symptoms were positively associated with disordered eating in the third trimester of pregnancy. There were no studies that examined obsessive‐compulsive symptoms during the post‐partum period.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…One fair‐quality cross sectional study found that obsessive‐compulsive symptoms was positively associated with disordered eating during pregnancy above 28 weeks gestation (Mohamadirizi et al, ). Similarly, Goncalves et al () identified that increased obsessive‐compulsive symptoms were positively associated with disordered eating in the third trimester of pregnancy. There were no studies that examined obsessive‐compulsive symptoms during the post‐partum period.…”
Section: Resultsmentioning
confidence: 87%
“…Again, only one study examined direction of association with disordered eating during the first/second trimester of pregnancy, positively predicting increased anxiety during the third trimester of pregnancy (Easter et al, ). Two fair‐quality cross sectional studies also supported an association between anxiety and disordered eating during the third trimester of pregnancy (Goncalves et al, ) and at 16 and 36 weeks gestation (Soares et al, ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, stress and related constructs appear to alter overall energy intake through under-or overeating, depending on the nature of the stressor, its severity as well as an individual predisposition 7 . In a cross-sectional study in pregnant women, emotional problems and negative attitudes towards the baby were related to dietary behavior, as was the pre-pregnancy body mass index 8 . Apart from stress, a meta-analysis suggests that depression is linked to weight and weight gain in a bidirectional manner 9 .…”
mentioning
confidence: 99%